Interfacial Reaction Boosts Thermal Conductance of Room‐Temperature Integrated Semiconductor Interfaces Stable up to 1100 °C - Xiaoyang Ji; Zifeng Huang; Yutaka Ohno; Koji Inoue; Yasusyohi Nagai; Yoshiki Sakaida; Hiroki Uratani; Jinchi Sun; Naoteru Shigekawa; Jianbo Liang; Zhe Cheng (Advanced Electronic Materials)
Abstract Overheating has emerged as a primary challenge constraining the reliability and performance of next‐generation high‐performance (ultra)wide bandgap (WBG or UWBG) electronics. Advanced heterogeneous bonding of high‐thermal‐conductivity WBG thin films and substrates not only constitutes a pivotal technique for fabricating these electronics but also offers potential solutions for thermal management. This study presents the integration of 3C‐silicon carbide (SiC) thin films and diamond substrates through a surface‐activated bonding technique. Notably, following annealing, the interfaces between 3C‐SiC and diamond demonstrate an enhancement in thermal boundary conductance (TBC), reaching up to ≈300%, surpassing all other grown and bonded heterointerfaces. This enhancement is attributed to interfacial reactions, specifically the transformation of amorphous silicon into SiC upon interaction with diamond, which is further corroborated by picosecond ultrasonics measurements. After annealing at 1100 °C, the achieved TBC (150 MW m−2 K−1) is among the highest among all bonded diamond interfaces. Additionally, the visualization of large‐area TBC, facilitated by femtosecond laser‐based time‐domain thermoreflectance measurements, shows the uniformity of the interfaces which are capable of withstanding temperatures as high as 1100 °C. The research marks a significant advancement in the realm of thermally conductive WBG/substrate bonding, which is promising for enhanced cooling of next‐generation electronics.